Breastfeeding Education: disagreement of meanings - Caicedo Martínez, Nydia Stella; Carrillo Pineda, Marcela; Gómez Dávila, Joaquín Guillermo (Investigación y Educación en Enfermería, 2016)
Objective. This work sought to analyze how educational processes have been developed for breastfeeding in a health institution, starting from the meanings mothers, families, and health staff construct thereon. Methods. This was qualitative research of ethnographic approach, which included observations during the group educational activities of the programs, focal groups, and interviews of mothers, their families, and the health staff of a hospital unit in the city of Medellín, Colombia. The analysis was guided by the constant comparison method. Results. The categories emerging from the data were: 1) breast milk is an ideal food. 2) The mothers’ experiences influence upon the breastfeeding practice. 3) Family beliefs sometimes operate as cultural barriers. 4) Disagreements are revealed in the educational process. Conclusion. The way educational processes have taken place for breastfeeding reveals a break expressed by the scarce interaction between the meanings professionals have constructed on the topic and those the mothers and their families give to the experience of breastfeeding. How to cite this article: Caicedo NS, Carrillo M, Gómez JG. Breastfeeding Education: disagreement of meanings. Invest. Educ. Enferm. 2016; 34(2):